2020
DOI: 10.1212/wnl.0000000000009178
|View full text |Cite
|
Sign up to set email alerts
|

Pearls & Oy-sters: Progressive ataxia and palatal tremor

Abstract: Palatal tremor (PT) (or myoclonus) is a rare movement disorder comprising 2 forms: essential PT (EPT) and symptomatic PT (SPT). c The rhythmic movement of the PT may be unilateral or bilateral with partial or complete rhythmicity. During sleep, tremor ceases in EPT but not in SPT. c Treatment for SPT includes medication such as valproate, clonazepam, or trihexyphenidyl; botulinum toxin has been successful in only a few reported cases. Oysters c Examination of the palate and careful review of imaging should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Palatal tremor (PT) comprises of two different entities: symptomatic palatal tremor (SPT) and essential palatal tremor (EPT). Palatal tremor may be unilateral, bilateral or asymmetrical 3 . Palatal movement in EPT results from activity of the tensor veli palatini muscle innervated by trigeminal nerve 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Palatal tremor (PT) comprises of two different entities: symptomatic palatal tremor (SPT) and essential palatal tremor (EPT). Palatal tremor may be unilateral, bilateral or asymmetrical 3 . Palatal movement in EPT results from activity of the tensor veli palatini muscle innervated by trigeminal nerve 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging brain showed hypertrophy of the bilateral inferior olivary nuclei (►Fig. 1).…”
Section: Palatal Myoclonus After Posterior Fossa Surgery In a Child W...mentioning
confidence: 99%
“…The familial variant of PAPT shows brainstem and cervical cord atrophy but no HOD [10,68,70]. Sporadic PAPT shows mostly bilateral HOD.…”
Section: Investigations (Table 4)mentioning
confidence: 99%
“…Rossi et al reported a mild improvement of gait instability but not the palatal tremor after treatment with chenodeoxycholic acid in a patient with PAPT secondary to cerebrotendinous xanthomatosis [68]. Nasal sumatriptan 20 mg temporarily helped palatal tremor although lamotrigine and clonazepam were found to be ineffective [70]. Drugs that can reduce the electronic coupling among the hypetrophic olivary neurons by blocking the connections (quinine or mefloquine) are suggested to control the symptoms although no study is available to support this [28].…”
Section: Treatmentmentioning
confidence: 99%